The Correlation between Critical and Creative Thinking Skills to Learning Outcomes in Cell and Tissue Materials - Nur Aisyah Ainun; Arsad Bahri; Andi Asmawati Azis (Program Studi Pendidikan Biologi FKIP Unpatti, 2025)
Optimizing student competence begins with empowering fundamental skills, namely critical and creative thinking skills. This study aims to investigate the correlation between critical thinking skills and creative thinking skills simultaneously on cognitive learning outcomes of 162 students in grades XI and XII who have learned cell and tissue material at the Movement School in Biringkanaya District, Makassar City in the even school year 2022/2023. Research data were collected using integrated essay questions as many as 10 items that were valid (4.73) and reliable (0.853). The data obtained from the research sample in the form of quantitative data will be analyzed with two kinds of analysis techniques, namely descriptive analysis and inferential analysis. The results of statistical inferential analysis showed a correlation between critical thinking skills, creative thinking skills, and cognitive learning outcomes of students in movement schools on cell and tissue material (=0.730, <0.001, N= 162). The correlation is positive with a regression equation Ŷ= 7.796 + 0.322X1 + 0.402X2 with an effective contribution of 53.26%. Therefore, learning needs to empowering critical and creative thinking skills to support the optimization of students in facing the challenges of everyday life problem.